The integration dimensions as part of food acculturation process: Exploratory factor analysis (EFA) approach / Noriza Ishak and Adilah Ramli - Ishak, Noriza; Ramli, Adilah (2016)
Acculturation is a process of adopting the cultural norms of the dominant group while maintaining their minority culture of origin and vice versa. As part acculturation process, integration or synthesis of the two cultures which is also termed as biculturalism occurs when individuals seek both to maintain their culture as well as daily participation in becoming part of the larger host society. This paper assessing the proposed determinants or dimensions of integration as part of food acculturation namely food knowledge, food media and food for social events using fifty-eight adapted and newly developed items. Through Principal component factor analysis with varimax rotation and factor loading of 0.50, the food knowledge dimension converged into three factors namely education, reading and language while food for social events and food media produced a single dimension. Thus, this integration constructs although require further confirmation could be used as predictors for the formation of commonly acceptable food and constructing the nation food identity.